A worldwide survey on proctological practice during COVID‐19 lockdown (ProctoLock 2020): a cross‐sectional analysis. (27th October 2020) - Gallo, Gaetano; Sturiale, Alessandro; De Simone, Veronica; Di Tanna, Gian Luca; Giani, Iacopo; Grossi, Ugo; ,
Abstract: Aim: Proctology is one of the surgical specialties that has suffered the most during COVID‐19 pandemic. Using a cross‐sectional non‐incentivised World Wide Web survey, we aimed to snapshot the current status of proctological practice in six world regions. Method: Surgeons affiliated to renowned scientific societies with an interest in coloproctology were invited to join the survey. Members of the ProctoLock Working Group enhanced recruitment by direct invitation. The predictive power of respondents' and hospitals' demographics on the change of status of surgical and outpatient activities was calculated. Results: Respondents ( n = 1050) were mostly men (79%), with a mean age of 46.9 years, at consultant level (79%), practising in academic hospitals (53%) offering a dedicated proctology service (68%). A total of 119 (11%) tested positive for SARS‐CoV‐2. The majority (54%) came from Europe. Participants from Asia reported a higher proportion of unaltered practice (17%), while those from Europe had the highest proportion of fully stopped practice (20%). The likelihood of ongoing surgical practice was higher in men (OR 1.54, 95% CI 1.13–2.09; P = 0.006), in those reporting readily availability of personal protective equipment (PPE) (OR 1.40, 1.08–1.42; P = 0.012) and in centres that were partially or not at all involved in COVID‐19 care (OR 2.95, 2.14–4.09; P < 0.001). This chance decreased by 2% per year of respondent's age ( P = 0.001). Conclusion: Several factors including different screening policies and resource capacity affected the current status of proctological practice. This information may help health authorities to formulate effective preventive strategies to limit curtailment of care of these patients during the pandemic.